Review of recent trends in optimization techniques for plug-in hybrid, and electric vehicle charging infrastructures - Rahman, I. (Elsevier Ltd, 2016)
For the consideration of environmental aspects of the personal transportation, electric vehicle (EV) and plug-in hybrid electric vehicle (PHEV) has the prospective solution nonetheless there is an obstacle to access the charging system plug. Additionally, the charging system delivers its own troubles when we compared it with petrol station since the participation of the different charging alternative. For the last few years, the studies associated with optimization of PHEV/EV charging infrastructure have drawn the researcher's consideration. New challenges and chances for the growth of smart grid technologies depend upon the recently introduced electric vehicle charging infrastructure services. In this particular review study, the literature bearing on the use of optimization methods for charging infrastructure is considered. Â© 2016 Elsevier Ltd. All rights reserved.